The Effect of Return on Equity, Net Profit Margin and Gross Profit Margin on Stock Prices in Mining Companies - Agustini; Wicaksono, Teguh; Ariani, Gusti Meinar Girda (CV ODIS, 2024)
This study aims to test and analyze the effect of Return On Equity, Net Profit Margin and Gross Profit Margin on stock prices in mining companies in the coal sub-sector for the 2019-2023 period. The research method used is a quantitative approach and is included in the type of quantitative associative research using documentation techniques. The population of this study amounted to 31 companies using purposive sampling technique so as to obtain 8 company samples and 40 total research samples. The analysis technique in this study uses descriptive statistics, classical assumption test, multiple linear regression analysis, hypothesis testing and determination coefficient test through the SPSS program. The results of this study indicate that Return On Equity has a significant effect on stock prices in coal sub-sector mining companies for the 2019-2023 period, Net Profit Margin has no significant effect on stock prices in coal sub-sector mining companies for the 2019-2023 period, Gross Profit Margin has no significant effect on stock prices in coal sub-sector mining companies for the 2019-2023 period, Return On Equity, Net Profit Margin and Gross Profit Margin simultaneously have a significant effect on stock prices in coal sub-sector mining companies for the 2019-2023 period.